2021
DOI: 10.1088/1757-899x/1145/1/012015
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Study on Axial Compressive Behaviour of CFST and Externally Wrapped CFRP Columns

Abstract: Concrete column fails by crushing or bucking due to axial load in order to resist failure of confinement, concrete filled steel tubular column (CFST) and carbon fibre reinforced polymer (CFRP) wrapping are used. CFST member has its consecutive progression in the construction industries due to its high load carrying capacity upgraded ductile performance, need for form work is minimized and has greater confinement effect. CFRP wrapping provides resistance towards corrosion, light weight exceptional durability, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The utilization of Fayalite slag in concrete clinker formation and the impacts of copper slag on the properties of concrete have been examined by numerous analysts [22][23][24]. A few works detailed the mechanical properties of concrete prepared using fayalite slags substitution for sand, and crushed stones show more development than ordinary cement [25][26][27]. For each huge load of copper delivered, roughly 2.2 to 3 tons of slags were created according to a logical estimate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of Fayalite slag in concrete clinker formation and the impacts of copper slag on the properties of concrete have been examined by numerous analysts [22][23][24]. A few works detailed the mechanical properties of concrete prepared using fayalite slags substitution for sand, and crushed stones show more development than ordinary cement [25][26][27]. For each huge load of copper delivered, roughly 2.2 to 3 tons of slags were created according to a logical estimate.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it creates an interest in concrete innovation and is relied upon to work on the mechanical properties. The impact of copper slag as a partial substitution for sand on high-performance concrete was examined by different researchers [25][26][27]. As a primer work, an ideal amount of copper slag to be utilized in the research was examined and found as forty percentage substitutions is the perfect material for fine aggregate substitution.…”
Section: Introductionmentioning
confidence: 99%